Wide-temperature-range high-iodine-loading positive electrode material, preparation method thereof and zinc-iodine battery
By using iodine-loaded positive electrode materials prepared in zinc-iodine batteries with iodine-loaded carbon black and gelatin binders, the problems of multi-iodide shuttle and zinc negative electrode in zinc-iodine batteries are solved, and higher cycle stability and energy density are achieved.
Patent Information
- Application Number
- CN202510105662.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-23
AI Technical Summary
Zinc-iodine batteries face problems of multi-iodide shuttle and unstable zinc negative electrodes, which limit their large-scale application.
By mixing activated carbon and iodine element and then heating the product, the iodine-loaded carbon black I2@CB is obtained, and mixed with the gelatin binder solution to form an iodine-positive electrode slurry. Finally, through coating and drying treatment, a wide temperature domain high-iodine-loaded positive electrode material was prepared.
This material constrains active iodine and adsorbs polyiodide through the active functional groups of gelatin adhesive, effectively inhibiting the dissolution of active iodine and the shuttle of polyiodide, and improving the cycle stability and energy density of zinc-iodine batteries.
Smart Images

Figure CN119764429A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a wide-temperature range high-iodine-loading positive electrode material, a preparation method thereof, and a zinc-iodine battery. Background Art
[0002] Intrinsically safe aqueous batteries are one of the important directions for the development of high-energy and high-safety energy storage batteries. Compared with lithium / sodium-ion batteries that use organic electrolytes, there are risks of flammability and explosion, and 70% of lithium and cobalt resources rely on imports. Aqueous batteries have the characteristics of low cost, high safety, environmental friendliness, and easy operation in the air. It is one of the important directions for the development of high-safety energy storage batteries. Aqueous zinc batteries use high-capacity metal zinc negative electrodes (820mAh / g) and are compatible with the working window of aqueous electrolytes. They are a hot topic in the research of aqueous batteries. Traditional zinc-based batteries use embedded positive electrode materials, which have low zinc storage capacity and slow kinetics. They do not match the high capacity of zinc negative electrodes and cannot give full play to the real advantages of aqueous zinc batteries. Therefore, it is urgent to develop new positive electrode material reactions. Halogen electrode reactions generally have faster kinetics due to the solubility of halogens. Among them, zinc-iodine batteries realize electrochemical energy storage through a conversion reaction mechanism, which gets rid of the energy storage method of traditional zinc-ion batteries that mainly relies on ion embedding and extraction, and avoids the problem of structural collapse of positive electrode materials in traditional zinc-ion batteries. In addition, iodine's low cost, abundant reserves, multivalent properties and high theoretical specific capacity (211 mAh / g) make zinc-iodine batteries one of the candidates for the next generation of clean and efficient energy storage devices.
[0003] However, zinc-iodine batteries still face serious problems of poly-iodide shuttling and unstable zinc negative electrodes, which limit the large-scale application of zinc-iodine batteries. The reason for these problems is that the iodine positive electrode undergoes a solid-liquid phase transition during the charging and discharging process. The solid iodine molecules are discharged into soluble iodide ions, which react with iodine molecules to form soluble poly-iodides. The poly-iodides dissolved in the electrolyte diffuse to the zinc negative electrode side and react irreversibly with zinc, causing corrosion of the zinc negative electrode and loss of iodine active substances, limiting its practical application. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a wide temperature range high iodine loading positive electrode material and a preparation method thereof and a zinc-iodine battery. The present invention mixes activated carbon and iodine element and then performs a heat treatment to obtain iodine-loaded carbon black I2@CB; then the iodine-loaded carbon black I2@CB, a conductive agent and a gelatin binder solution mixed with acetic acid are mixed to obtain an iodine positive electrode slurry; finally, the iodine positive electrode slurry is coated and dried to obtain a wide temperature range high iodine loading positive electrode material. The wide temperature range high iodine loading positive electrode material prepared by the present invention effectively inhibits the problems of active iodine dissolution and polyiodide shuttling by utilizing the active functional groups of gelatin in the gelatin binder solution, such as peptide bonds, carboxyl groups, and amino groups, to restrain active iodine and chemically adsorb polyiodides.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first object of the present invention is to provide a method for preparing a wide temperature range high iodine loading positive electrode material, comprising the following steps:
[0007] S1. After mixing activated carbon and iodine, heat treatment is performed to sublime the iodine and embed it into the activated carbon to obtain iodine-loaded carbon black I2@CB; wherein the mass ratio of activated carbon to iodine is 1 to 1.5:1; the greater the porosity of iodine-loaded carbon black, the more iodine it carries, the greater the proportion of active substances in the wide temperature range and high iodine loading positive electrode material, and the higher the energy density.
[0008] S2. Mix gelatin and acetic acid solution to obtain a gelatin binder solution.
[0009] S3, mixing the iodine-loaded carbon black I2@CB, the conductive agent and the gelatin binder solution to obtain an iodine positive electrode slurry.
[0010] S4. Coat the iodine positive electrode slurry on a stainless steel mesh and dry it to obtain a positive electrode material with a wide temperature range and high iodine loading.
[0011] Preferably, the conditions for the heating treatment are: heating at 100°C to 140°C for 6h to 8h in a closed container; within this temperature range, iodine is sublimated into vapor and diffuses into the pores of the activated carbon, and then condenses into solid iodine after cooling, thereby achieving iodine loading in the activated carbon; and the closed container is to prevent iodine from sublimating into vapor and overflowing.
[0012] Preferably, in the gelatin binder solution, the mass percentage of gelatin is 2wt% to 6wt%; wherein, when the mass percentage of gelatin exceeds 6wt%, the gelatin binder solution will be too viscous, and it will be difficult to mix evenly after adding the conductive agent and the iodine-loaded carbon black I2@CB; and when it is less than 2wt%, the slurry will be too thin, and the slurry will not be well coated on the current collector. In addition, gelatin has low solubility in water, is easy to gel, and has high viscosity. Using acetic acid solution as a solvent makes the wide temperature range high iodine loading positive electrode material have better viscosity and processing technology; and gelatin contains rich polar functional groups, including peptide bonds, amino groups and carboxyl groups, and has good wettability with the aqueous electrolyte of zinc-iodine batteries, which is conducive to forming a good positive electrode interface and reducing ion transfer impedance.
[0013] Preferably, the mass ratio of iodine-loaded carbon black I2@CB, conductive agent and gelatin binder solution is 7-8:1.5-2:0.5-1; the conductive agent is evenly mixed with the iodine-loaded carbon black I2@CB and gelatin binder solution to achieve smooth electron transmission, and the binder can provide sufficient adhesion to firmly bond the iodine-loaded carbon black I2@CB, the conductive agent and the current collector.
[0014] Preferably, the iodine is also ground for 1 to 3 minutes to form a fine powder. The grinding time cannot be too long to prevent the iodine from sublimating. The iodine of the present invention is a particle slightly larger than sesame seeds. In order to mix evenly with the activated carbon and accelerate sublimation, it must be ground first.
[0015] Preferably, the conductive agent is selected from Ketjen black or conductive carbon materials.
[0016] Preferably, the drying conditions are: drying at 25°C to 35°C for 1 h to 2 h.
[0017] Preferably, the solvent in the acetic acid solution is water, and the mass fraction of acetic acid in the acetic acid solution is 75% to 80%.
[0018] Preferably, the current collector is selected from stainless steel mesh or titanium foil.
[0019] The second object of the present invention is to provide a wide temperature range high iodine loading positive electrode material prepared by the above preparation method.
[0020] The third object of the present invention is to provide a zinc-iodine battery, which is a button battery or a soft-pack battery, and is composed of the above-mentioned wide temperature range high iodine loading positive electrode material, a diaphragm and a negative electrode material and an electrolyte.
[0021] Preferably, the button battery consists of a button battery shell, a gasket and a spring, a glass fiber separator, a ZnSO4 electrolyte, a wide temperature range high iodine loading positive electrode material and a zinc foil disc negative electrode.
[0022] Preferably, the soft-pack battery is composed of a glass fiber separator, a ZnSO4 electrolyte, a wide temperature range high iodine loading positive electrode material and a zinc foil negative electrode.
[0023] Preferably, the soft pack battery is prepared according to the following steps:
[0024] An aluminum current collector is welded on the wide temperature range high iodine loading positive electrode material, and a copper-plated nickel current collector is welded on the negative electrode. The positive electrode, separator, and negative electrode are stacked in sequence, and an aluminum-plastic film is inserted. One end of the aluminum current collector and the copper-plated nickel current collector is led out, and the electrolyte is poured in and hot-pressed for packaging.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention provides a method for preparing a wide temperature range high iodine loading positive electrode material, wherein activated carbon and iodine are mixed, and then subjected to a heating treatment to sublimate the iodine and embed it into the activated carbon to obtain iodine-loaded carbon black I2@CB; wherein the mass ratio of activated carbon to iodine is 1 to 1.5:1; gelatin and acetic acid solution are mixed to obtain a gelatin binder solution; iodine-loaded carbon black I2@CB, a conductive agent and a gelatin binder solution are mixed to obtain an iodine positive electrode slurry; the iodine positive electrode slurry is coated on a stainless steel mesh, and subjected to a drying treatment to obtain a wide temperature range high iodine loading positive electrode material. The wide temperature range high iodine loading positive electrode material prepared by the present invention can improve the binding ability of the wide temperature range high iodine loading positive electrode material to active iodine and the chemical adsorption effect on polyiodides by utilizing the active functional groups of gelatin in the gelatin binder solution, such as peptide bonds, carboxyl groups, and amino groups, thereby effectively inhibiting the problems of active iodine dissolution and polyiodide shuttling.
[0027] 2. The wide temperature range high iodine loading positive electrode material provided by the present invention has good performances of high loading capacity, high cycle capacity and long life. Gelatin is used as a binder for the wide temperature range high iodine loading positive electrode material, so that the wide temperature range high iodine loading positive electrode material can work in a wide temperature range of -10°C to 60°C. Gelatin exhibits effective chemical adsorption characteristics for polyiodides. This mechanism significantly inhibits the shuttle effect, thereby reducing the loss of active substance iodine, directly improving the capacity performance of the wide temperature range high iodine loading positive electrode material and enhancing its cycle stability. In addition, due to its inherent high viscosity, gelatin can form a thicker wide temperature range high iodine loading positive electrode material layer during the preparation process, which provides a larger loading space for iodine, thereby achieving a higher iodine loading.
[0028] 3. The zinc-iodine battery provided by the present invention has excellent anti-self-discharge capability, high rate performance and long-lasting cycle stability in a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1This is a comparison chart of the cycle performance of the wide temperature range high iodine loading positive electrode material prepared in Example 1 and the iodine positive electrode material prepared in Comparative Example 1 in zinc-iodine batteries, wherein a is 25°C, b is 60°C, and c is -10°C.
[0030] Figure 2 This is a cycling performance diagram of the wide temperature range high iodine loading positive electrode material prepared in Example 1 at high loading and 2C rate.
[0031] Figure 3 This is a comparison chart of the anti-self-discharge performance of the wide temperature range high iodine loading positive electrode material prepared in Example 1 and the iodine positive electrode material prepared in Example 1.
[0032] Figure 4 The adsorption performance diagram of the gelatin binder solution prepared in Example 1 and the PTFE binder prepared in Comparative Example 1, wherein a is the adsorption performance of the gelatin binder solution prepared in Example 1 and the PTFE binder prepared in Comparative Example 1. 3- The adsorption of 3- Color comparison chart of solution before and after adsorption; b is the adsorption of I2, and the inset is the color comparison chart of I2 solution before and after adsorption.
[0033] Figure 5 The contact angle diagram between the wide temperature range high iodine loading positive electrode material prepared in Example 1 and the iodine positive electrode material prepared in Ratio 1 and the electrolyte, wherein a is PTFE and b is Gelatin. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods. Among them, polytetrafluoroethylene is denoted as PTFE.
[0036] In the prior art, zinc-iodine batteries face serious problems of multiple iodide shuttling and unstable zinc negative electrodes, which limit the large-scale application of zinc-iodine batteries. Traditional methods focus on improving the electrolyte formula, optimizing the battery structure or developing new additives, but these methods are often difficult to fundamentally solve the problems of active iodine dissolution and multiple iodide shuttling. In recent years, improving the cycle stability and energy density of zinc-iodine batteries by designing high-performance positive electrode materials has become a research hotspot. Among them, using porous carbon materials as iodine carriers and fixing iodine molecules by physical adsorption or chemical bonding can effectively reduce iodine dissolution and shuttling effects. However, simple physical adsorption is not enough to maintain the stability of iodine for a long time, especially under high temperature or long-term cycle conditions.
[0037] In view of the above technical defects, the present invention provides a method for preparing a wide temperature range high iodine loading positive electrode material, comprising the following steps: after mixing activated carbon and iodine element, heating treatment is performed to sublimate the iodine element and embed it into the activated carbon to obtain iodine-loaded carbon black I2@CB; wherein the mass ratio of activated carbon to iodine element is 1 to 1.5:1; after mixing gelatin and acetic acid solution, a gelatin binder solution is obtained; iodine-loaded carbon black I2@CB, a conductive agent and a gelatin binder solution are mixed to obtain an iodine positive electrode slurry; the iodine positive electrode slurry is coated on a stainless steel mesh, and dried to obtain a wide temperature range high iodine loading positive electrode material. The wide temperature range high iodine loading positive electrode material prepared by the present invention effectively inhibits the problems of active iodine dissolution and polyiodide shuttling by utilizing the active functional groups of gelatin in the gelatin binder solution, such as peptide bonds, carboxyl groups, and amino groups, to restrain active iodine and chemically adsorb polyiodides.
[0038] The technical solution of the present invention is further explained by using embodiments below, which are specifically as follows:
[0039] Example 1
[0040] A method for preparing a wide temperature range high iodine loading positive electrode material comprises the following steps:
[0041] S1. After mixing activated carbon and iodine in a mass ratio of 1:1, add the mixture into a mortar and grind for about 2 minutes until the mixture is fine. Then, take the mixture out and add it into a glass sample bottle, place it into a forced air drying oven and heat it at 120°C for 6 hours to allow the iodine to sublime and embed into the activated carbon to obtain iodine-loaded carbon black I2@CB.
[0042] S2. Prepare acetic acid solution according to the mass ratio of acetic acid to water of 8:2, weigh type A gelatin and dissolve it in the acetic acid solution, then heat it in a water bath at 60°C for 2h to obtain a gelatin binder solution, wherein the mass fraction of type A gelatin in the gelatin binder solution is 5wt%.
[0043] S3. Weigh iodine-loaded carbon black I2@CB, Ketjen black and gelatin binder solution respectively, the mass ratio of iodine-loaded carbon black I2@CB, Ketjen black and gelatin binder solution is 7:2:1, then put them into a mortar and grind them for 5 minutes. During the process, acetic acid solution is added to adjust the viscosity of the iodine positive electrode slurry, and continue wet grinding for 2 minutes to obtain iodine positive electrode slurry.
[0044] S4. Coat the iodine positive electrode slurry on a stainless steel mesh and place it in an oven to dry at 25°C for 2 hours to obtain a positive electrode material with a wide temperature range and high iodine loading, which is denoted as Gelatin.
[0045] Example 2
[0046] A method for preparing a wide temperature range high iodine loading positive electrode material comprises the following steps:
[0047] S1. After mixing activated carbon and iodine in a mass ratio of 1.5:1, add the mixture into a mortar and grind for about 2 minutes until the mixture is fine. Then, take the mixture out and add it into a glass sample bottle, place it into a forced air drying oven and heat it at 100°C for 8 hours to allow the iodine to sublime and embed into the activated carbon to obtain iodine-loaded carbon black I2@CB.
[0048] S2. Prepare acetic acid solution according to the mass ratio of acetic acid to water of 8:2, weigh type A gelatin and dissolve it in the acetic acid solution, then heat it in a water bath at 60°C for 2h to obtain a gelatin binder solution, wherein the mass fraction of type A gelatin in the gelatin binder solution is 6wt%.
[0049] S3. Weigh iodine-loaded carbon black I2@CB, Ketjen black and gelatin binder solution respectively, the mass ratio of iodine-loaded carbon black I2@CB, Ketjen black and gelatin binder solution is 7:2:1, then put them into a mortar and grind them for 5 minutes. During the process, acetic acid solution is added to adjust the viscosity of the iodine positive electrode slurry, and continue wet grinding for 2 minutes to obtain iodine positive electrode slurry.
[0050] S4. Coat the iodine positive electrode slurry on a stainless steel mesh and place it in an oven to dry at 25°C for 2 hours to obtain a positive electrode material with a wide temperature range and high iodine loading.
[0051] Example 3
[0052] A method for preparing a wide temperature range high iodine loading positive electrode material comprises the following steps:
[0053] S1. After mixing activated carbon and iodine in a mass ratio of 1:1, add the mixture into a mortar and grind for about 2 minutes until the mixture is fine. Then, take the mixture out and add it into a glass sample bottle, place it into a forced air drying oven and heat it at 140°C for 6 hours to allow the iodine to sublime and embed into the activated carbon to obtain iodine-loaded carbon black I2@CB.
[0054] S2. Prepare acetic acid solution according to the mass ratio of acetic acid to water of 8:2, weigh type A gelatin and dissolve it in the acetic acid solution, then heat it in a water bath at 60°C for 2h to obtain a gelatin binder solution, wherein the mass fraction of type A gelatin in the gelatin binder solution is 2wt%.
[0055] S3. Weigh iodine-loaded carbon black I2@CB, Ketjen black and gelatin binder solution respectively, the mass ratio of iodine-loaded carbon black I2@CB, Ketjen black and gelatin binder solution is 8:1.5:0.5, then put them into a mortar and grind them for 10 minutes. During the process, acetic acid solution is added to adjust the viscosity of the iodine positive electrode slurry, and continue wet grinding for 5 minutes to obtain iodine positive electrode slurry.
[0056] S4. Coat the iodine positive electrode slurry on a stainless steel mesh and place it in an oven to dry at 35°C for 1 hour to obtain a positive electrode material with a wide temperature range and high iodine loading.
[0057] Comparative Example 1
[0058] A method for preparing an iodine-loaded positive electrode material comprises the following steps:
[0059] S1. After mixing activated carbon and iodine in a mass ratio of 1:1, add the mixture into a mortar and grind for about 2 minutes until the mixture is fine. Then, take the mixture out and add it into a glass sample bottle, place it into a forced air drying oven and heat it at 60°C for 6 hours to allow the iodine to sublime and embed into the activated carbon to obtain iodine-loaded carbon black I2@CB.
[0060] S2. Weigh iodine-loaded carbon black I2@CB, Ketjen black and PTFE binder respectively, with the mass ratio of iodine-loaded carbon black I2@CB, Ketjen black and PTFE binder being 7:2:1, and then put them into a mortar and grind them for 5 minutes. During the process, water is continuously added to adjust the viscosity of the iodine positive electrode slurry to obtain a positive electrode slurry.
[0061] S3. Coat the positive electrode slurry on a stainless steel mesh, and place it in an oven at 25° C. to 35° C. to dry for 2 h to obtain an iodine-loaded positive electrode material, which is recorded as PTFE.
[0062] Application method:
[0063] The wide temperature range high iodine loading positive electrode material prepared in Example 1 and the iodine-loaded positive electrode material prepared in Comparative Example 1 are respectively used as positive electrode sheets and placed in the center of the positive electrode shell. A small amount of 2 mol / L ZnSO4 electrolyte is dripped, a glass fiber diaphragm is loaded, and the electrolyte is continued to be dripped until it is soaked. A zinc foil disc is taken and aligned with the position of the positive electrode sheet and loaded into the battery shell. A gasket and a spring are placed, and the battery sealing machine is used to package them to obtain zinc-iodine button batteries, which are respectively recorded as Gelatin-button battery and PTFE-button battery.
[0064] observe Figure 1It is concluded that the present invention improves the electrochemical performance of zinc-iodine batteries by selecting gelatin as a functional binder. Compared with the commonly used polytetrafluoroethylene (PTFE) binder, the battery cycle capacity of the battery using the gelatin binder solution is higher and the cycle life is longer, whether tested at room temperature (25°C), high temperature (60°C) or low temperature (-10°C). After 14,000 cycles of 10C charge and discharge at room temperature, the discharge capacity of the Gelatin-button battery is 123mAh / g, while the PTFE-button battery fails after about 9,000 cycles, and the discharge capacity before failure is only 96mAh / g.
[0065] observe Figure 2 It was concluded that type A gelatin, as a binder, can be used to make a high-load iodine positive electrode. When the iodine loading is about 10 mg, it can still stably cycle nearly 700 times under 2C conditions, and the specific capacity remains at 124 mAh / g.
[0066] observe Figure 3 It was concluded that the gelatin binder solution also has an advantage in resisting self-discharge. After the zinc-iodine button battery was charged to 1.6V and then left to stand for 48 hours, the voltage of the PTFE-button battery dropped to 1.268V, while the Gelatin-button battery still maintained 1.315V, indicating that the Gelatin-button battery has strong resistance to self-discharge.
[0067] Adsorption test:
[0068] The gelatin adhesive solution prepared in Example 1 was dripped onto a glass sheet and dried to obtain a gelatin adhesive film. 3- Weigh an equal mass of PTFE binder powder and add 3- After 30 minutes of rest, the color change of the solution was observed, and the I3 in the solution was quantitatively characterized by UV-visible spectroscopy. - Among them, I3 - It is formed by the reaction of 8mmol / L I2 and 8mmol / L KI dissolved in water, and its concentration is 8mmol / L.
[0069] observe Figure 4 The illustration of Figure a shows that in the brown I 3- After the gelatin binder solution prepared in Example 1 was added to the solution for adsorption, a brown-yellow color was obtained. 3- The color of the solution becomes lighter, and the Figure 4 The UV-visible absorption spectrum results in Figure a show that the gelatin binder solution can reduce I 3- The aggregation density is 3-It has a strong chemical adsorption effect, weakens its diffusion to the negative electrode, and inhibits the shuttle effect. It adsorbs I2 and reduces the dissolution of active iodine; observe Figure b in 4, after adding the gelatin binder solution prepared in Example 1 to the I2 solution, the color of the I2 solution gradually becomes clear, indicating that the concentration of I2 in the I2 solution is greatly reduced.
[0070] Depend on Figure 5 to obtain, to observe Figure 5 Figure a shows that the contact angle of the PTFE binder is 41°, while the abundant polar functional groups in type A gelatin, such as peptide bonds, amino groups, and carboxyl groups, make the wide temperature range high iodine loading cathode material have good affinity with the electrolyte, and the contact angle is 0, such as Figure 5 As shown in Figure b, it can reduce the impedance at the interface and improve the performance of zinc-iodine button batteries.
[0071] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0072] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a wide temperature range high iodine loading positive electrode material, characterized in that: The following steps are involved: After the activated carbon and the iodine element are mixed, they are heated to sublime the iodine element and embed it into the activated carbon, thereby obtaining iodine-loaded carbon black I2@CB; wherein the mass ratio of the activated carbon to the iodine element is 1 to 1.5:1; After mixing gelatin and acetic acid solution, a gelatin binder solution is obtained; The iodine-loaded carbon black I2@CB, a conductive agent and a gelatin binder solution are mixed to obtain an iodine positive electrode slurry; The iodine positive electrode slurry is coated on the current collector and dried to obtain a positive electrode material with a wide temperature range and high iodine loading.
2. The method for preparing a wide temperature range high iodine loading positive electrode material according to claim 1, characterized in that: The conditions for the heat treatment are: heating at 100°C to 140°C for 6h to 8h in a sealed container.
3. The method for preparing a wide temperature range high iodine loading positive electrode material according to claim 1, characterized in that: The mass ratio of iodine-loaded carbon black I2@CB, conductive agent and gelatin binder solution is 7-8:1.5-2:0.5-1.
4. The method for preparing a wide temperature range high iodine loading positive electrode material according to claim 1, characterized in that: In the gelatin binder solution, the mass percentage of gelatin is 2wt% to 6wt%.
5. The method for preparing a wide temperature range high iodine loading positive electrode material according to claim 1, characterized in that: The solvent in the acetic acid solution is water, and the mass fraction of acetic acid in the acetic acid solution is 75% to 80%.
6. A positive electrode material with a wide temperature range and a high iodine loading obtained by the method for preparing a positive electrode material with a wide temperature range and a high iodine loading according to any one of claims 1 to 5.
7. A zinc-iodine battery, characterized in that: The zinc-iodine battery is a button cell or a soft-pack cell, and is composed of the wide-temperature range high-iodine-loading positive electrode material as described in claim 5, a separator, a negative electrode material and an electrolyte.
8. The zinc-iodine battery according to claim 7, characterized in that: The button battery consists of a button battery shell, a gasket, a shrapnel, a glass fiber diaphragm, a ZnSO4 electrolyte, the wide temperature range high iodine loading positive electrode material according to claim 6, and a zinc foil disc negative electrode.
9. The zinc-iodine battery according to claim 7, characterized in that: The soft-pack battery is composed of a glass fiber separator, a ZnSO4 electrolyte, the wide temperature range high iodine loading positive electrode material as described in claim 6, and a zinc foil negative electrode.
Citation Information
Patent Citations
Lithium-sulfur battery positive plate and preparation method thereof
CN112002874A
Sodium-sulfur battery and preparation method thereof
CN112928262A
High-iodine-loading carbon material composite positive electrode, aqueous zinc ion iodine secondary battery and preparation method
CN116864603A
Activated carbon-elemental iodine composite material and preparation method thereof, positive electrode and zinc-iodine battery
CN118899418A
Lithium / iron sulfide primary battery
JP2007109526A
Cited By
Conductive-agent-free iodine positive electrode based on PEDOT: PSS and preparation method and application of conductive-agent-free iodine positive electrode
CN120854468A
Wide-temperature-range miniature zinc-iodine battery and preparation method thereof
CN121769280A